Indoor PM2.5and its Polycyclic Aromatic Hydrocarbons in Relation with Incense Burning - Susira Bootdee (2018)
© Published under licence by IOP Publishing Ltd. This study aims to determine fine particulate matter (PM2.5) and polycyclic aromatic hydrocarbons (PAHs) emitted from incense burning to assess human health risk. PM2.5samples were collected for 8 hrs and 24 hrs during special occasions and normal period from two shrines in the city of Chiang Mai, Thailand. PM2.5-bound PAHs were extracted and analyzed by GC-MS. The highest average PM2.5concentrations were found during Chinese New Year (625±147 μg/m3(8 hrs) and 406±159 μg/m3(24 hrs)). The highest total PAHs concentrations were also found during the same period (168±60 ng/m3for 8 hrs and 102±26 and for 24 hrs). Concentrations of PM2.5and carcinogenic-PAHs were highly correlated (r = 0.451-0.802) and were high during special occasions particularly during Chinese New Year due to high number of visitors and amount of incense being burned. The toxicity equivalent (TEQ) values were also relatively high during Chinese New Year (31-32 ng/m3(8 hrs) and 10-20 ng/m3(24 hrs)). It can be revealed that incense burning emits air pollutants and can increase degree of indoor air pollution and human health risk.